Influencer Attributes and Purchase Intentions in Indonesian Luxury Market: A Case of Gadgetin and iPhone - Kristina, Katharina (Journal of Business, Management, and Social Studies, 2024)
Objective The objectives of this study are to determine the effect of an influencer’s attractiveness on the intention of Indonesian customers to purchase a luxury product, explore the relationship between an influencer’s expertise and Indonesian customers’ desire to purchase luxury brands, and to investigate the impact of an influencer’s trustworthiness on Indonesians’ intentions to purchase luxury brands. Methodology Partial Least Squares (PLS) with SmartPLS software was used to examine the research model. The sample of the study are 50 to 100 respondents. This study used a quantitative approach in the form of an online questionnaire to investigate the effects of YouTube videos on luxury brand purchase intention. Findings Influencer attractiveness and trustworthiness have positive effects on purchase intention, whereas expertise, despite having a negative impact, is still statistically significant. Novelty This research offers a unique contribution by examining the specific context of luxury brands in Indonesia and delving into the nuances of the influencer attributes (attractiveness, expertise, and trustworthiness).